Edukasi Mari Kenali Gempa Bumi: Siap Menghadapi dan Tetap Tenang - Namah, Cindy Trivena; Pello, Shela C. (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Indonesia is a country with a high potential for earthquakes due to the movement of tectonic plates. Earthquakes can affect mental health, especially in children, who are a vulnerable group. Education about disaster preparedness is very important to increase children's knowledge about actions to be taken when an earthquake occurs and reduce anxiety. Objective: The aim of this educational activity is to introduce the concept of earthquakes and deep breathing relaxation techniques Method: This activity is carried out with lectures and discussions, and focuses on preventive measures and ways to overcome anxiety Result: The results of this educational activity, let's recognize earthquakes, show an increase in children's understanding of earthquakes and relaxation techniques to calm themselves. Conclusion: This educational activity in Benteng Kuwu Village received a positive response, showing the importance of further education for disaster preparedness for children.